2022
DOI: 10.3390/ijerph191710969
|View full text |Cite
|
Sign up to set email alerts
|

Illness Experience and Quality of Life in Sjögren Syndrome Patients

Abstract: Sjögren’s syndrome (SS) is a disease with autoimmune features that affects mainly women and compromises the health-related quality of Life (HRQoL); it is important to evaluate illness experience for a better understanding of the life situation of the patient. The aim of the study was to summarize the individual life experiences and determine the impact of HRQoL and oral health-related quality of life (OHRQoL) and their correlation with health self-assessment in women with SS. The life experiences evaluation em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…It revealed a significant increase in their OHIP-14 scores compared to the initial assessment, especially in relation to the physical pain and psychological discomfort subscales [ 7 ]. Similarly, the findings of a recent study showed that OHRQoL in pSS seemed to be frequently impaired, with physical pain and psychological discomfort being the most affected OHIP-14 dimensions, which coincided with our results [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…It revealed a significant increase in their OHIP-14 scores compared to the initial assessment, especially in relation to the physical pain and psychological discomfort subscales [ 7 ]. Similarly, the findings of a recent study showed that OHRQoL in pSS seemed to be frequently impaired, with physical pain and psychological discomfort being the most affected OHIP-14 dimensions, which coincided with our results [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…Sjogren's syndrome (SS) is a high-rate, common, and harmful global disease with higher potential morbidity and is an essential menopausal and aging disease [34][35][36]. The disease is characterized by xerostomia with dysfunction of salivary gland secretion as the initiating factor, which affects the whole body's health [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Current limitations in robust screening tools and definitive protocols for DED assessment exacerbate the challenge. Additionally, the profound impact of SS on a patient's quality of life may often be underestimated by clinicians, leading to reduced referrals for comprehensive evaluations [6].…”
Section: Prevalencementioning
confidence: 99%